Characterization of the complete chloroplast genome of Hordeum jubatum (Poaceae: Pooideae: Triticeae) and phylogenetic analysis. Issue 10 (3rd October 2021) - Chen, Zhenjiang; Jin, Yuanyuan; Li, Xiuzhang; Wei, Xuekai; Li, Chunjie; White, James F.; Nan, Zhibiao
Abstract: Hordeum jubatum is a salt tolerant forage, which plays an important role in improving saline-alkali land and animal husbandry alkali-saline grassland. Hordeum jubatum has been gradually domesticated as an ornamental grass due to its special flower color. However, no domesticated varieties of H. jubatum plant have been reported worldwide. This study reported the complete chloroplast genome of wild H. jubatum, which was 136, 871 bp in length, containing a pair of inverted repeats (IRA/IRB) of 21, 608 bp separated by a small single-copy (SSC) area region of 12, 799 bp and the large single-copy (LSC) region of 80, 856 bp. A total of 133 genes, including 85 protein-coding genes (79 PCG species), 40 transfer RNA genes (32 tRNA species), and eight ribosomal RNA genes (four rRNA species) were predicted from the chloroplast genomes. The overall GC content was 38.25%, and the corresponding values of the LSC, SSC, and IR were 36.22%, 32.15%, and 43.85%, respectively. The phylogenetic analysis showed that wild H. jubatum was clustered closely with Hordeum bogdanii .